How readers' perceived self-congruity and functional congruity affect bloggers' informational influence: Perceived interactivity as a moderator. Issue 4 (10th August 2015) - Wang, Shih-Ju; Hsu, Chiu-Ping; Huang, Heng-Chiang; Chen, Chia-Lin
Abstract : Purpose: – The purpose of this paper is to treat bloggers as human brands and applies self-congruity theory to explore how actual and ideal blogger-reader self-congruity, combined with the blog's functional congruity, influences blogger-reader relationship quality (BRRQ) and the blogger's informational influence, taking perceived interactivity among blog members as a moderator. Design/methodology/approach: – Using a survey of 372 female beauty blog readers, this study employs the structural equation modelling approach to investigate the proposed model. Findings: – The empirical findings indicate that readers' perceived self-congruity with beauty bloggers raises the bloggers' informational influence, mediated by BRRQ and functional congruity. Actual self-congruity has greater predictive power than ideal self-congruity in explaining bloggers' informational influence. Moreover, perceived interactivity plays a two-sided role because it strengthens the positive impact of BRRQ on informational influence but weakens the positive impact of functional congruity on informational influence. Practical implications: – The findings should help marketers identify influential beauty bloggers through their presented image on their blogs to encourage readers' acceptance of their opinions about products and services. However, when focusing on beauty blogs featuring high-perceived interactivity among blog members, marketers should carefully balance the facilitating and offsetting effect of perceived interactivity and identify bloggers equipped with superior BRRQ. Originality/value: – Using human brand and parasocial interaction perspectives, this study contributes to emerging research on human brands and blog marketing and demonstrates that perceived interactivity is a double-edged sword in stimulating a blogger's informational influence.